THE MINIMALIZATION OF FILTER EQUIPMENT FOR TRACTION SUBSTATIONS USING BOOSTER CONVERTER - Goncharov, Yu. P.; Zamaruev, V. V.; Ivahno, V. V.; Liubych, R. I.; Panasenko, N. V. (Science and Transport Progress, 2009)
The structure of traction substation 3,2 kV DC power source is considered. It is shown that the output filter choke of traction substation with voltage added converter may be excluded. A dynamic model of voltage added converter is developed, its features, as an active filter, are described.